Sgp120 and the contact system in hereditary angioedema: A diagnostic tool in HAE with normal C1 inhibitor. (March 2020) - Larrauri, Blas; Hester, C. Garren; Jiang, Haixiang; Miletic, Vojislav D.; Malbran, Alejandro; Bork, Konrad; Kaplan, Allen; Frank, Michael
Highlights: sgp120 has been identified as ITIH4, can be cleaved by kallikrein, and can be used to study contact system activation. sgp120 fragmentation and spontaneous contact system activation is present in the plasma of a majority of HAE-C1inh patients. sgp120 fragmentation and contact system activation occur in a majority of HAE-nl-C1inh samples after cold incubation. The loss of C1 inhibitor function and C1 inhibitor fragmentation occur in HAE-nl-C1inh samples after cold incubation. sgp120 (ITIH4) may be a potential biomarker for the laboratory diagnosis of HAE-nl-C1inh. Abstract: Mutations in Factor XII, plasminogen gene, angiopoietin-1 gene and kininogen 1 gene have been found in some patients with hereditary angioedema with normal C1 inhibitor (HAE-nl-C1inh), but the underlying disease mechanisms remain unclear. Additionally, there are no accepted biomarkers for this disease. Because the contact system has been implicated in hereditary angioedema with C1 inhibitor deficiency (HAE-C1inh), we studied the fragmentation patterns of serum glycoprotein 120 (sgp120), a protein that is highly susceptible to cleavage by kallikrein, in 31 HAE-C1inh and 13 HAE-nl-C1inh patient plasma samples. Compared to normal controls, the majority of plasma samples from patients with HAE-C1inh contained fragmented sgp120. These samples also showed increased kallikrein amidolytic activity indicating spontaneous contact system activation. In contrast, most samples from HAE-nl-C1inh patients exhibited intact sgp120. However, if these samples were incubated at 4 °C in plastic, significant sgp120 fragmentation and spontaneous contact system activation were observed. Concurrently, there was C1 inhibitor fragmentation that generated the nonfunctional 94 kD fragment and a reduction in C1 inhibitor function. Normal samples did not show sgp120 or C1 inhibitor fragmentation after incubation. We sequenced sgp120 and found it to be identical to inter-alpha-trypsin inhibitor heavy chain 4 (ITIH4). These results suggest that sgp120 or ITIH4 is cleaved when the contact system is activated and that this cleavage could be used as a biomarker in patients with HAE-nl-C1inh.